Professional Development of Teachers in Islamic Boarding Schools through Training in Literacy-Based Innovative Learning Strategies - Indana, Sifak; Dayu, Dian Permatasari Kusuma; Ainiyah, Nur; Ichsan, Mochammad; Pratiwi, Dwi Setyo; Maladona, Adi (DIKDIMAS : Jurnal Pengabdian Kepada Masyarakat, 2025)
Background: This community service activity was conducted at Islamic Boarding School An-Nur 2 Al-Murtadlo and involved IPAS teachers at the junior and senior secondary levels. Literacy, especially scientific literacy, has not been optimally integrated into IPAS learning. Therefore, strengthening teachers’ pedagogical competence through innovative and contextual learning strategies aligned with the characteristics of the pesantren environment is essential to foster a sustainable literacy culture.Aims: The innovative learning strategies training aimed to improve students’ literacy, which remains low, particularly in the pesantren context.Methods: This study employed a quantitative survey method. The training was conducted using the Project-Based Learning (PjBL) model, which actively involved teachers in designing innovative literacy-based learning. Data were collected through a four-point Likert scale questionnaire and analyzed using mean scores, percentages, and predetermined effectiveness criteria.Results: The results of the study indicate that the training was categorized as very effective across all measured indicators. The mean scores for each indicator ranged from 3.25 to 3.38 out of a maximum score of 4.00, corresponding to percentage values between 81.3% and 84.5%. The overall mean score was 3.32 (83.0%).Conclusion: The training effectively enhanced teachers’ pedagogical competence and supported literacy development in the pesantren context through PjBL and digital literacy integration. It also contributed to the development of a sustainable literacy culture in Islamic boarding schools.